Arabic Learning for Academic Purposes - Fatoni, Ahmad (Izdihar : Journal of Arabic Language Teaching, Linguistics, and Literature, 2019)
This study aimed to determine the goal of teaching Arabic for Academic purposes. Teaching Arabic for non-Arabic speakers is generally divided into two types: Arabic language for life, which is a public program in which multiple attributes are related. Learning Arabic is only intended to communicate with Arabic in different situations of life. The second type is Arabic language programs for special purposes, including Arabic for academic purposes (AAP), Arabic for Businessmen People (ABP), Arabic for Education People (AEP), Arabic for Objective Purposes (AOP) and others. The researcher in this article focused on the Arabic language teaching program for academic purposes. The method used for this study was carried out using descriptive analysis method which the data were collected from personal interview with students of University of Darussalam Gontor and some documents. The result showed that the successful of teaching Arabic language for academic purposes related to use Arabic language in daily life as well as special activities such as scientific discussions.